Sleep problems were unrelated to social media use in the late COVID-19 pandemic phase: A cross-national study - Tore Bonsaksen; Daicia Price; Gary Lamph; Isaac Kabelenga; Amy Østertun Geirdal (PLoS ONE, 2025)
Sleep problems are commonly related to stress and mental health problems. However, social media use has become widespread in the general population during recent years, and their addictive potential may influence people’s sleep routine. In addition, the COVID-19 pandemic gave rise to substantial mental health problems in the population, and restrictions in social life gave social media a unique position as means for both entertainment and interpersonal contact. The aim of the study was to examine sleep problems in relationship to social media use in a cross-national sample two years after the COVID-19 outbreak. Participants were 1405 adults from four countries who completed a cross-sectional online survey. The data were analyzed with independent samples t-tests, Chi Squared tests of independence, and single and multivariable logistic regression analyses. Of the 858 (61.1%) participants who reported sleep problems during the past weeks, a substantial proportion (n = 353, 41.1%) related their sleep problems to their experience with COVID-19. With adjustments for age, gender, employment, and psychological distress, more hours of daily social media use was not significantly associated with sleep problems. However, higher age (OR: 1.13, p = 0.01), female gender (OR: 1.69, p<0.001), having employment (OR: 1.34, p = 0.04), and higher levels of psychological distress (OR: 1.20, p<0.001) were independently associated with sleep problems. While the debate about the pros and cons of social media use continue, this study suggests that higher levels of social media use was not of great concern for people’s sleep quality in the late COVID-19 pandemic phase. However, other aspects of social media use (eg, time of the day, content of interactions, associated stress experience) may be more relevant for understanding sleep problems and may be taken into consideration for people who experience such problems.